Analyzing Work Productivity and Program Quality in Collaborative Programming - Duque, R.; Bravo, C. (2008 Third International Conference on Software Engineering Advances, 2008)
Pair programming practices usually take place on a single computer where two programmers collaborate, taking on the roles of driver and observer. This article presents COLLECE, a groupware system to support synchronous distributed pair programming practices, and includes a variety of experimental activities in which two groups of programmers were involved to solve various programming problems. The first group carried out the activities by employing distributed pair programming practices using COLLECE, while the second group of solo programmers followed traditional programming practices. These experimental activities were used to conduct comparative studies of work productivity and program quality.